Effect of Relaxation Therapy on Anxiety Level and Breast Milk Production in Pregnant and Postpartum Mothers: Systematic Literature Review - Mutiara Ayu Muthiatulsalimah; Rr Sri Endang Pujiastut; Aris Santjaka; Runjati Runjati (Publikasi Indonesia, 2022)
Anxiety in pregnant and postpartum women can affect the condition of the mother and baby. Psychological stress can influence the hypothalamus and pituitary gland to secrete Adrenocorticotropic Hormone to produce cortisol. The amount of cortisol is high, resulting in inhibited milk production. Relaxation therapy is able to stimulate the milk ejection reflex more efficiently than standard practice in health care facilities which only focus on optimizing body functions, without involving the mind and soul. This review conducted a systematic review to evaluate the effect of interventions using Relaxation Therapy in increasing breast milk production. A literature search was conducted using the PRISMA guidelines including studies of relaxation therapy interventions during the pregnancy and postpartum period. Using a literature keyword search strategy, 718 studies related to relaxation therapy in pregnant and postpartum women were found and 25 studies were eligible for inclusion in the analysis. A total of 10 studies on anxiety in pregnant women, 5 studies on anxiety in postpartum mothers, 3 studies on cortisol hormone levels, 5 studies on breast milk production and 2 studies on prolactin hormone levels. These studies were conducted in Malaysia, France, England, Greece, Korea, Turkey, America, Taiwan, Iran, Indonesia, Spain, Denmark and India. The samples analyzed were 1,608 pregnant women and 1227 postpartum women. Based on the results of a review, Relaxation Therapy in the form of Hypnobreastfeeding and Music Therapy is effective in stimulating the production of breast milk and prolactin hormones in postpartum mothers. Hypnosis, Music Therapy and Benson's relaxation technique were associated with a significant reduction in anxiety levels as indicated by an increase in PSS scores and a decrease in salivary cortisol.